QUALITY ASSURANCE PROCESSES IN HIGHER EDUCATION SYSTEMS IN ARMENIA AND ENGLAND (Education in the 21st Century, 2022)
Within the framework of the research, we briefly studied the quality assurance processes in the higher education systems of Armenia and England. The research was based on the following tasks: to carry out a comparative analysis of the quality assurance processes in Armenia and England and to present suggestions aimed at improving quality assurance. The aim of the research is to reveal the peculiarities, similarities, differences and their reasons between the higher education quality assurance processes of the two countries.Both Armenia and England, being a member of the Common European Higher Education Area, have similarities due to the Bologna process, as well as in the processes of ensuring the quality of higher education. In addition to the quality assurance standards and their national education systems standards, both countries are guided by the European Quality Assurance Standards and Guidelines - EQASG.Examining the quality assurance processes in higher education in Armenia and England, we have come to the conclusion that regardless of the country's governance, development, socio-economic and cultural differences there are a number of similarities among the EBRD member countries within the framework of Bologna process and that allows for comparable education degrees and comparable qualifications. In contrast to Armenia, quality assurance processes in the UK are largely regulated by universities and accreditation is not mandatory for universities unless they receive state funding. As a result of the research, we concluded also that the educational policy pursued by England is more effective in terms of quality teaching, which, within the country, sorts the universities and their qualifications according to the university ratings and the order of the educational degree awarded to the students according to the student's academic progress.
Keywords: higher education; quality assurance; accreditation; institutional accreditation; european higher education area; self-analysis; academic expertise